(untitled) (Світ фінансів, 2018)
Чеберяко О. В., Куліш М. О. Необхідність та результативність проведення фінансової децентралізації. Розглянуто поточний стан, основні тенденції та початкові результати фінансових аспектів реалізації реформи місцевого самоврядування в Україні. Проаналізовано причини необхідності проведення фінансової децентралізації. Визначено фактори, що призвели до зміни таких показників місцевих фінансів, як джерела їх формування, розмір власних надходжень та видатків місцевих бюджетів, їх частка в зведеному бюджеті України. Проведено аналіз чинників, що стимулюють та заважають органам місцевого самоврядування щодо добровільного об’єднання громад. Розглянуто зміни до процесу бюджетування на місцевому рівні, які будуть здійснюватися виконавчими органами в середньостроковій перспективі. Чеберяко О. В., Кулиш М. А. Необходимость и результативность проведения финансовой децентрализации. Рассмотрено текущее состояние, основные тенденции и начальные результаты финансовых аспектов реализации реформы местного самоуправления Украины. Проанализированы причины необходимости проведения финансовой децентрализации. Определены факторы, которые привели к изменению таких показателей местных финансов, как источники их формирования, размер собственных доходов и расходов местных бюджетов, их доля в сводном бюджете Украины. Определены принципы формирования и эффективность функционирования новой административно-территориальной единицы – объединенных территориальных общин. Проведен анализ факторов, стимулирующих и мешающих органам местного самоуправления к добровольному объединению общин. Рассмотрены изменения в процесс бюджетирования на местном уровне, которые будут осуществляться исполнительными органами в среднесрочной перспективе. Сформированы выводы относительно необходимых способов оптимизации дальнейшего процесса децентрализации в Украине. Cheberyako O., Kulish M. Necessity and results of financial decentralization. Introduction. Local budgets are the most numerous link of the budget system, the financial base of local authorities, which plays a decisive role in implementing regional policy through financing public expenditures and are the key to the emergence of a capable and efficient local government. However, the unsatisfactory results of the local authorities functioning in previous periods have led to the objective need to reform existing structure of local finances through fiscal decentralization. Purpose.To characterize the essence of financial decentralization from the point of view of its necessity for the economy of territorial and administrative units development and to analyze the success and risks of its implementation in Ukraine. Methods. In the course of writing the article, several methods were used. Among them were the method of analysis and synthesis, scientific comparison, formal logic and dialectics. Results. It has been determined that since the beginning of financial decentralization, the share of local budgets in the consolidated budget of Ukraine has doubled. The local budget revenues has increased in 2.8 times. Facts above indicate increasing in financial resources available to local authorities and, accordingly, more equal distribution of powers and opportunities of local and state authorities. The financial capacity of local budgets is evidenced by the balance of funds on accounts, which at the end of 2017 were amounted to 78.1 billion UAH. As a result, due to the accumulated resources of local budgets, more expenditure responsibilities has been given to local authorities. In addition, since the beginning of 2015, the formation of united territorial communities has begun, of which 699 had been formed by the end of 2017, but only 159 of them are fully operational. However, despite of the results achieved, significant financial, administrative and political factors threaten to continue fiscal decentralization. Conclusion. Despite the successful implementation of financial reform for local budgets, neglecting obvious risks can have a significant impact on the budgetary system of Ukraine. Therefore, the state and local authorities should further strengthen the requirements for the quality of community associations, control over their implementation and more objective planning and analysis of the results achieved, as the shortcomings in the reform will tend to be strengthened and may have a synergistic effect.